Quantum Theory of Recollisional (e, 2e) Process in Strong Field Nonsequential Double Ionization of Helium - Chen, Zhangjin; Liang, Yaqiu; Lin, C. D. (My University, 2010)
Based on the full quantal recollision model and field-free electron impact ionization theory, we calculate the correlated momentum spectra of the two outgoing electrons in strong field nonsequential double ionization (NSDI) of helium to compare with recent experiments. By analyzing the relative strength of binary versus recoil collisions exhibited in the photoelectron spectra, we confirm that the observed fingerlike structure in the experiment is a consequence of the Coulomb interaction between the two emitted electrons. Our result supports the recollision mechanism of strong field NSDI at the most fundamental level.